The company we keep [compact disc, unabridged] : a husband-and-wife true-life spy story - Baer, Robert (Random House Audio, 2011)
For twenty years Robert Baer and his wife Dayna worked as operatives for the CIA. Here the couple shares how they were able to balance the intense world of spying with the everyday issues that regular families encounter on a daily basis.